Experimental Study on Mechanical Properties of Integrated Wall Panels of Grain Warehouse with “Thermal Insulation” - Xuesen Li; Yonggang Ding; Jinquan Zhao; Qikeng Xu (Advances in Civil Engineering)
The walls of grain cottage silos are still being built by clay brick masonry featured with single-structure form, poor air tightness, large workload of manual masonry on site, and huge consumption of raw materials and burning materials, which is not conducive to energy saving and environmental protection. In order to study the mechanical function of the new wall under the action of grain side pressure, the static loading test was conducted on the model of scaled-down wall panel under the action of side pressure. The damage process, the damage pattern, and the bearing capacity of the wall panel were studied through the analysis of the crack development process and distribution law to reveal the force characteristics of the wall panel. The test results show that the span deflection of the “structure-insulation” integrated wall panel under the lateral pressure meets the requirement of the limit state of normal use; the inner and outer leaf wall panels can work together under the action of the joint; the ratio of the load borne by the inner and outer leaf wall panels is equal to the ratio of their stiffness; the flexural stiffness of the wall panels after cracking is proposed based on the combined effect analysis. Based on the analysis of the combined effect, the degradation factor of the wall panel after cracking is proposed, and the deflection calculation formula of the inner and outer leaf wall panel is established, which provides a theoretical basis for the design and the promotion of the “structure-insulation” integrated wall panel.